Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-02-17T16:06:07+01:00

Resolvamos y comprobemos :

a)  (1/2)x +3*(x+1) = 2

      (x/2) + 3*(x+1) = 2

[(x+  6*(x+1)]/2 = 2

    (x+6x+6)/2 = 2

     (7x+6) = 2*(2)

       7x+6 = 4

            7x = 4-6

              7x = -2

                 x = -2/7

Comprobemos :

(1/2) * (-2/7) + 3*(-2/7  +1) = 2

   -2/14  + 3*(5/7) = 2

   -1/7 + (15/7 ) = 2

     (-1+15)/7 = 2

          14/7 = 2

               2 = 2  --->   ComprobaDo :)

b) 2*(2x-5) = 3x-1

      4x -10 = 3x -1

       4x -3x = -1+10

                x = 9

Ahora comprobemos :

2*[2*(9) -5] = 3*(9) -1

  2*[ 18-5] = 27-1

   2*[13] = 26

         26 = 26   ---> ComproBaDo :)

c) (-6/5)x = x+2

      -6x/5 = x+2

      -6x = 5*(x+2)

    -6x = 5x+10

    -6x -5x =10

        -11x= 10

               x = -10/11

Comprobemos:

(-6/5) * (-10/11) = (-10/11) +2

  (60/55) = (-10+22)/11

    (12/11) = (12/11)  ----> ComprobaDo, SaLuDos :)'